2016
DOI: 10.1111/apt.13521
|View full text |Cite
|
Sign up to set email alerts
|

I148M variant of PNPLA3 increases the susceptibility to non‐alcoholic fatty liver disease caused by obesity and metabolic disorders

Abstract: SUMMARY BackgroundThe patatin-like phospholipase 3 (PNPLA3) rs738409 gene polymorphism is an important genetic determinant of non-alcoholic fatty liver disease (NAFLD). However, the associations between liver fat and metabolic traits in rs738409 G allele carriers and the allelic influence on this association have not been fully studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 52 publications
1
28
0
1
Order By: Relevance
“…the I148M variant in PNPLA3 [27] and the E167K variant in TM6SF2 [28]. The frequency of the I148M gene variant has been reported to be 37.0% [29] and 38.0% [30] in Chinese and 37.9% in Europid subjects [31, 32]. The frequency of E167K gene variant has been reported to be 6.7% in the Chinese [33] and about 7% in Europid subjects [27,34,35].…”
Section: Discussionmentioning
confidence: 99%
“…the I148M variant in PNPLA3 [27] and the E167K variant in TM6SF2 [28]. The frequency of the I148M gene variant has been reported to be 37.0% [29] and 38.0% [30] in Chinese and 37.9% in Europid subjects [31, 32]. The frequency of E167K gene variant has been reported to be 6.7% in the Chinese [33] and about 7% in Europid subjects [27,34,35].…”
Section: Discussionmentioning
confidence: 99%
“…[10] Numerous studies have shown that PNPLA3 may be the most important gene for the occurrence for NAFLD, in particular, a nonsynonymous sequence variation (rs738409 C > G, I148M) in PNPLA3 has been identified to be strongly associated not only with steatosis but also with clinically relevant factors and the progression of NAFLD. [11,12] A GWAS from Kawaguchi et al [8] had revealed several SNPs, including rs2896019 and rs3810622 in the PNPLA3 gene, were associated with the histological classifications of NAFLD in the Japanese population. Kitamoto et al [13] also discovered that these 2 SNPs were associated with the progression of simple steatosis to NASH and the development of NAFLD.…”
Section: Introductionmentioning
confidence: 99%
“…Participants The Shanghai Changfeng Community Study recruited 4300 Chinese community residents (1652 men, 2648 women) aged >45 years from May 2010 to December 2012. Participants with medical records or self-reports of previous viral hepatitis, excessive alcohol consumption and chronic liver diseases other than NAFLD were excluded [14]. In the current study, we report the first-round follow-up results of the Changfeng large-scale community study.…”
Section: Methodsmentioning
confidence: 99%
“…In one largescale cohort study in Germany, the PNPLA3 rs738409 G variant was found to be associated with increased liver diseaseassociated mortality but reduced coronary heart diseaseassociated mortality [12]. Adiposity can amplify the effect of the PNPLA3 rs738409 C>G variant on liver fat accumulation according to recent studies [13][14][15]. Weight gain is the most important risk factor for both NAFLD [16] and type 2 diabetes [17].…”
Section: Introductionmentioning
confidence: 99%